The Effect of IBA and NAA on Root Induction of Tithonia diversifolia (Hemsl.) - Ramadhani, Dwi Nova; Hidayati, Irul; Faizah, Hanik (Biotropika: Journal of Tropical Biology, 2025)
Tithonia diversifolia (Hemsl.) is a plant that has a lot of potential for use in several sectors, so that large-scale and short-time propagation efforts are needed. Tissue culture is an appropriate technique for cultivating Tithonia diversifolia plants. The success of root induction in tissue culture is largely determined by the auxin growth regulator. This study aimed to determine the effect of IBA and NAA on root induction of T. diversifolia plants. The method was an experimental study with a Completely Randomised Design (CRD). Tithonia diversifolia plant node explants were planted into Murashige and Skoog (MS) media supplemented with growth regulators IBA (1 and 2 mg/L), NAA (1 and 2 mg/L), and a combination of IBA and NAA (1 mg/L + 1 mg/L; 1 mg/L + 2 mg/L; 2 mg/L + 1 mg/L; and 2 mg/L + 2 mg/L) and control group, consisting of explants cultured on a hormone-free medium which were then incubated for 4 weeks. The observation data were analysed statistically using the non-parametric Kruskal-Wallis test, followed by the Mann-Whitney test. The results showed that all parameters significantly affected auxins IBA and NAA in the root induction of T. diversifolia plants. The NAA 2 ppm treatment was the most effective in terms of root emergence time (3.67 DAP). Additionally, the combination of IBA and NAA was the optimal treatment in terms of root growth percentage (1.00%). The IBA 2 ppm + NAA 2 ppm treatment yielded the best results in terms of root number (10.17 strands). The NAA 1 ppm treatment yielded the best results in terms of root length (11.3 cm), root fresh weight (0.0967 g), and root dry weight (0.0144 g).